Development of the Nile Littoral Cell during the past 8.2 kyr. (15th December 2021) - Bookman, Revital; Mor-Federman, Tsofit; Herut, Barak; Harlavan, Yehudit; Taha, Nimer; Stein, Mordechai; Almogi-Labin, Ahuva
Abstract: The depositional history of the Nile Littoral Cell (NLC) in the past 8.2 kyr was reconstructed from two radiocarbon-dated cores retrieved down-flow the Nile Delta at the southeastern Mediterranean-Levantine continental shelf. The two cores are located ∼80 km apart at the inner shelf off-shore Israel: core V115 at a southern proximal site and core V101 at a northern distal site. Grain-size distribution, chemical composition, and εNd and 87 Sr/ 86 Sr isotope ratios and marine derived variables such as carbonate content, total organic carbon and its δ 13 C composition record the temporal and spatial variations in transport processes and sediment provenance. From ∼8.2 to ∼5.5 ka BP the record is dominated by coarse quartz sands from the Nile Delta front that were recycled along the NLC due to shelf transgression along with the post glacial sea level rise. Oligotrophic conditions prevailed in the inner shelf, and the relatively high carbonate content reflects the decrease in Nilotic fine particles due to increased vegetation and decrease in surface erosion related to the African Humid Period (AHP) wetter conditions. The chemical and isotope signature of the fine fractions indicates mostly remobilization of dust-driven surface cover soils from the surrounding lands that originated from the granitoid terrains of the Sahara-Arabia deserts. Sea level stabilization, termination of the AHP at ∼5.5 ka BP and the partial drying of the Ethiopian Highlands resulted in the increase of fine sediments with a basaltic signature. After ∼5.5 ka BP, fine sediments were supplied seasonally by the Nile, creating a distinct mud belt along the Israeli coast and Nile Delta at water depth exceeding ∼35 m. Occasional sediment coarsening in the distal NLC likely reflects periodical decrease in Nile floods discharge or contribution from shallower water depth due to increased storminess. With the continuation of the regional aridification and decreasing intensity of the Nile River flow during the last 2 kyr, higher contribution of surface cover particles from the nearby lands was recorded in the distal northern site, while the southern site continued to be affected mostly by the Nilotic contribution. A distinct increase in grain size and carbonate content, and decrease in TOC content and δ 13 Corg values at the topmost part of the sedimentary record represent the Nile River damming during the modern period, which resulted in halting of the Nile fine suspension and lead to ultra-oligotrophic conditions in the Levantine basin. Highlights: Depositional history of the Holocene Nile Littoral Cell off Israel. Provenance of fine detritus sediments by Nd and Sr isotope ratios. Major sources of fine detritus from the Sahara deserts and Nile Valley. Sediment long-shore transport during post glacial transgression. Mud belt development at the mid-shelf during the last 5.5 kyr.